Grundtvigs optegnelser med titlen: Irenæus. Transkriberet og kommenteret - Kiel, Ulla (Grundtvig-Studier, 1997)
Grundtvig’s Notes Entitled Irenæus By Vila Kiel In 1824 Grundtvig bought a book at an auction, written by Irenaeus, the Church Father, namely ≫Adversus Haereses≪ (Against Heresies). Grundtvig published a translation of the 5th Book of this work in 1827 under the title ≫On the Resurrection of the Body and its Share in God’s Kingdom≪ There is further written evidence of Grundtvig’s interest in Irenaeus. Thus the Manuscript Archives in The Royal Library has a number of notes written by Grundtvig. They are marked ≫Irenaeus≪ and are brief extracts and summaries of the 1st, 3rd and 4th Book of Irenaeus’s work ≫Against Heresies≪. The extracts and summaries show that Grundtvig was highly preoccupied with the Apostles’ Creed and its significance. Irenaeus calls the Creed ≫the rule of truth≪. It lays down guidelines for the interpretation of the Scriptures. It was characteristic of the heretics against whom his books are directed, that they interpreted the Bible arbitrarily. Ireneus has delightful examples of how such arbitrary use of the Bible may manifest itself. They behave as if one tears a beautiful picture of a king to pieces and then puts the pieces together again at random. The result is the picture of a fox! The reason is that a poor artist has been at work. He who does not know the original picture may thus be tricked into believing that the picture of the fox represents the king. He who knows the original picture will be able to recognize the pieces of the original work of art and will know that they have been put wrongly together. Grundtvig found that a similar use of the Bible occurred among the scholars of his own time. In 1825 he published ≫The Rejoinder of the Church≪, the polemical pamphlet against Professor H.N. Clausen. He dated it Irenaei Day which, according to the University Almanac, is the 26th of August.The dating in itself indicates Grundtvig’s interest in Irenaeus in this connection. Grundtvig’s notes may well belong in the same context.